JURIDICAL ANALYSIS OF FINTECH LENDING AGREEMENT BASED ON CIVIL LAW PERSPECTIVE IN INDONESIA - Dwi, Amelia; Efendi, Dr. Jonaedi (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The growth of fintech P2P lending is getting faster and easier to access for people who still struggle to get loans and for MSME entrepreneurs who need capital to develop their business. Investing in P2P lending offers the prospect of high returns annually, however, the investment must be in accordance with personal profile and risk appetite and how to manage it. Therefore, the objectives of this research is to find out the legal Tunaiku credit agreement based on the civil law perspective in Indonesia; legal consequences if one of the parties defaults on the credit agreement in this application; and find out the form of legal protection for other parties who are aggrieved in the application credit agreement. Analysis of legal materials using qualitative descriptive analysis with the type of normative legal research. In addition, the research approach used is a statutory approach, conceptual approach, and case study approach. Data sources were obtained from primary, secondary, and tertiary legal materials. The results of this research are (1) digital financial services activities are implemented in cooperation with third parties in the context of inclusive finance; (2) if there is a defaulted person, it is obliged to reimburse costs, losses, and interest due to non-fulfillment of an agreement in accordance with Article 1243 of the Civil Code; and (3) in order to obtain legal protection, the public is encouraged to choose a fintech lending company that has been registered with the Financial Services Authority.